Old Russian Cities of the East European Plain in the 10th century according to written sources (updating the perspective for research) - A. S. Shchavelev (Шаги)
The article provides an analytical review of references that contain oeconyms related to the people named Rus’ in the 10th century in Arabic, Byzantine, Old Russian and Old Scandinavian written traditions. Critical assessment of the identiﬁcation of oeconyms from these texts in different languages and from different times requires us to reject the historiographical inertia of perceiving urban history of the 10th century through the prism of the narrative of “The Primary Chronicle” from the beginning of the 12th century. If we don’t resort to the artiﬁcial etymological ﬁtting of oikonyms from different traditions, then out of 25 Old Russian annalistic names of cities 2 or 3 names are reﬂected in two treaties from 911 and the 930s — ﬁrst half of 940s, 1 name is reﬂected in an Arabic text from the 920–950s, 4 or 5 — in a Greek text from the 950s, 4 — in earlier Scandinavian texts, and 5 — in later texts. At least 10 oikonyms from the Arabic, Greek and Scandinavian writing traditions are not known to the earliest Russian Chronicles. A comparison of lists of oikonyms from different traditions allows us to suggest that they reﬂected three phases of the process of urbanization of Eastern Europe: the ﬁrst — the appearance of Scandinavian emporia in the 9th — ﬁrst half of the 10th century; the second — crystallization of the core of the Rurikid polity around Kyiv in the ﬁrst half of the 10th century; the third — the ﬁnal expansion of the Rurikids at the end of the 10th — middle of the 11th century. It was during the last stage when a “map” of Rus’ cities was formed that is reﬂected in “The Primary Chronicle” from the beginning of the 12th century, therefore it would be unjustiﬁed methodologically to project this late “map” onto earlier periods.